Nanoparticles for light management in ultrathin chalcopyrite solar cells. Issue 21 (10th November 2016) - Schmid, Martina; Manley, Phillip; Ott, Andreas; Song, Min; Yin, Guanchao
Abstract: Abstract : We evaluate the potential of inserting metallic, metal-dielectric core-shell, and fully dielectric nanoparticles in ultrathin chalcopyrite solar cells to enhance absorption which experiences a significant drop for absorber thicknesses below 500 nm. For different integration positions at the front or at the rear of the solar cell structure theoretical expectations and potential benefits originating from light scattering, near-field enhancement and coupling into waveguide modes by the nanoparticles are presented. These benefits are always balanced against experimental challenges arising for particular geometries due to the very specific fabrication processes of chalcopyrite solar cells. In particular high absorber deposition temperatures as well as contact layers that are relatively thick compared to other devices need to be considered. Based on this, we will need to go beyond some geometries that have proven beneficial for other types of solar cells and identify the most promising configurations for chalcopyrite-based devices.